RESISTING THE ALLURE OF FUTURE GENERATIONS’ “RIGHTS” - Pinto e Netto, Luísa (Pravni zapisi, 2026)
The language of future generations (FG) has become prominent in climate litigation; they are increasingly being treated as present rightsholders. Using a constitutional perspective, the paper argues that FG cannot function as present right- sholders since the category is legally vague, conceptually unstable, and epistemically indeterminate, preventing identification of rightsholders, specification of the scope of rights, and their operationalization in adjudication. The paper further shows that reliance on FG rights is neither necessary nor effective in tackling climate change, risking the shift of attention away from present duties and responsibility. Constitutional rights frameworks already contain objective norms and state duties that can safeguard future conditions without attributing rights to non-existing individuals. The paper argues we should resist the allure of FG rights and focus on legally coherent tools capable of advancing inter- and intragenerational justice.
Keywords: climate discourse; climate litigation; future generations; rightsholders; fundamental rights; objective dimension of fundamental rights